La eficacia de la adopción y el derecho de los menores a tener una familia. - Cuesta Calle, Soledad Karina (2023)
In Ecuador, the rights of children and adolescents are recognized in Ecuador’s Constitution (2008), in international conventions, treaties, national codes and laws, especially with regard to the right having a family, therefore it’s important that the academy investigate the effectiveness of adoption and the right of minors to have a family, This research focused on studying the adoption process in Ecuador and its effectiveness as a legal entity that protects the minors’ right of having a family. In the first part, the origin and development of the rights of children and adolescents in the progress of society were recorded, recognizing as a subject of rights, and creating the concept of adoption as a legal mechanism to protect their right to access a family. This legal concept is divided into two phases: administrative (as the head of the Technical Unit for Adoptions) and judicial, which is facilitated by the juvenile courts, which in Ecuador are known as the Judicial Unit for the Family of Women, Children and Adolescents. This research reviewed the requirements for initiating the adoption process and the process contained in the Organic Code for Children and Adolescents. Within the general context, the research has sought to know whether the adoption process protects the right of children and adolescents to have a family, and field research tools such as: Survey and interview of the Technical Adoption Unit of the Province of Ambato - Tungurahua and the Judicial Unit of the Family, Women, Children and Adolescents of Ambato Canton, Tungurahua province; collecting criteria and opinions of professionals who are immersed in the adoption processes in Zonal 3.